Migration from the Southern Mediterranean Countries. An Analysis of Some Macro Drivers. (1st October 2014) - Coderoni, Silvia; Perito, Maria Angela
Abstract : As a consequence of reduced precipitation and higher temperatures, the Mediterranean region over recent decades, has been exposed to major impacts of climate change, and these are likely to worsen as the climate continues to change. Global warming in regions that are highly dependent on agricultural production will generate changing land use patterns and trigger economy-wide effects. These environmental drivers will impact on other macro drivers of migration, increasing the number of people that might choose to leave their own native region. In this paper we analyse some emerging trends that, at the macro level, affect the main drivers of migration in North Africa and we try to envisage what could be an incipient problem, arising from concurrent local elements. Looking at some long-term trends in climate change and past evidence on food production and prices, we conclude that some environmentally-induced migration in the context of global environmental change is inevitable in the future, even if its scale is uncertain. Thus, the governance gap related to climate change migrants should be bridged, in order not to face a bigger challenge in the geo-political equilibrium of Mediterranean region.